Harmonic mitigation project, Work Package 1a: Literature review - Atheer Habash (2020)
This literature review addresses how distribution network connected inverters associated with renewable energy sources may provide harmonic compensation as an additional, or “ancillary service”. In other words, how inverters may be used as Active Filters while simultaneously delivering fundamental power.Current harmonics are caused by nonlinear devices connected to the power grid as they draw or inject non-sinusoidal currents when supplied with a sinusoidal voltage. These current harmonics interact with the power grid’s impedance to create voltage distortion that can adversely affect the distribution system’s equipment, and customer equipment that is connected to the system. Power quality standards have been developed for the UK system (currently G5/4-1, with G5/5 expected to be implemented during 2020) that define voltage distortion planning levels. Newly connected equipment is expected to be compliant.Mitigation of harmonics produced by connected non-linear equipment, loads or generation, can be achieved by installing either Passive Filters (combinations of inductive, capacitive and resistive components that sink the harmonic currents) or Active Filters (power converters controlled to inject current harmonics with opposing phase angles). Active Filters can either be standalone systems, or can be implemented as additional control algorithms placed within an existing power converter (the focus of this WPD innovation project).The main functional blocks required within an Active Filter controller are: harmonic current or voltage extraction to establish harmonic levels; a current loop controller to establish the required level of intervention; and gate signal generation to implement the required electrical intervention. This review details different implementations for each of these main functional blocks, together with advantages and disadvantages of each implementation.The review also identifies previous work that has investigated power converter controller implementations that deliver both fundamental power and harmonic mitigation. In these cases, active filtering is performed as an ‘ancillary service’. Three specific implementation examples are described in detail, together with simulation results. Each simulation shows the feasibility of mitigating harmonics and also illustrates: (i) the requirement to limit harmonic mitigation in coordination with fundamental power output, to operate the power converter within equipment ratings; and (ii) the ability of mitigating time-varying harmonics.Results from hardware implementations of Active Filter operation within multi-functional inverters are not very common in the literature, partly due to the novelty of this approach. However, two examples are presented that again show successful mitigation of harmonics (one with additional phase balancing functionality, and one for a hybrid wind–PV system). One further example is also presented where harmonic mitigation functionality was added to a STATCOM operating in south-west Scotland on a system that was experiencing voltage total harmonic distortion (THD) of up to 3.3%. With active filter functionality enabled, voltage THD was successfully reduced to around 1%.This literature review has provided a detailed summary of previous research and development that can beneficially be built upon in the work Swansea University are undertaking to develop an algorithm that can improve the network’s harmonic levels by controlling existing Distributed Generation inverters, acting individually or as a coordinated group.